CRITICAL SUCCESS FACTORS OF LEAN SIX SIGMA AND ITS RELATION ON OPERATIONAL PERFORMANCE OF SMES MANUFACTURING COMPANIES: A SURVEY RESULT - Ahmad, Md Fauzi; Zainudin, Mohamad Haziq Haikal; Abdul Hamid, Norhadilah; ahmad, Ahmad Nur Aizat; Abdul Rahman, Nor Aida; Mohd Nawi, Mohd Nasrun (International Journal of Supply Chain Management, 2019)
Many companies implement lean six sigma (LSS) approach aiming to improve business performance. However, not many companies can be benefited from this program as the implementation is not easy to be executed effectively. Thus, the objective of this study is to identify the important factors in LSS implementation and its relation on operational performance (OP) of the business. This study employed quantitative survey with structured questionnaire. Random sampling was used and the sample of this study was SME manufacturing companies which has implemented LSS approach. A set of questionnaires were sent out to 200 companies through email and targeted to LSS practitioners such as managing director, quality manager and production manager. Finally, 63 response have been received with 32% response rate. Statistical Package for the Social Science (SPSS) 22.0 version software was used to evaluate descriptive and the relationship between variables. This research studies the role of three factors in LSS implementation, which are management engagement and leadership, lean six sigma competency, and effective training and education. The findings revealed that there is a significant relationship between LSS factors with OP. Management engagement and leadership was the most perceived important factor in LSS implementation. This research model serve as a practical guide which can assist the company to achieve better operational business performance.